2021
DOI: 10.3389/fonc.2021.608608
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence of the Efficacy and Safety of Neoadjuvant EGFR-TKIs for Patients With Non-small Cell Lung Cancer

Abstract: PurposeEpidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been indicated to be an effective treatment for advanced EGFR-mutant NSCLC. However, the neoadjuvant application of EGFR-TKIs in resectable NSCLC needs further investigation. Here, we aimed to evaluate the efficacy and safety of neoadjuvant EGFR-TKIs for lung cancer.MethodsPublished studies on neoadjuvant EGFR-TKIs in NSCLC were identified in PubMed, Web of Science, and EMBASE until June 1, 2020. Data on surgical rates, objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The ORR of neoadjuvant EGFR- TKI in the EGFR-sensitive mutation population is 48% and early stage NSCLC may reduce the ORR of neoadjuvant EGFR-TKIs ( 23 ), and the MPR of neoadjuvant Osimertinib was 15% ( 5 ). However the evidence for neoadjuvant targeted therapy especially in these subgroups of EGFR mutation status, PD-L1 expression is still not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR of neoadjuvant EGFR- TKI in the EGFR-sensitive mutation population is 48% and early stage NSCLC may reduce the ORR of neoadjuvant EGFR-TKIs ( 23 ), and the MPR of neoadjuvant Osimertinib was 15% ( 5 ). However the evidence for neoadjuvant targeted therapy especially in these subgroups of EGFR mutation status, PD-L1 expression is still not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Sang-Won Um: If the tumor harbors sensitizing EGFR mutations or ALK rearrangements, targeted therapy seems to be a good option. However, previous studies about neoadjuvant EGFR-TKIs or ALK-TKIs were usually small sample sizes and single-arm studies (33,34). More data are needed to elucidate the exact role of EGFR-TKIs or ALK-TKIs in the neoadjuvant setting.…”
Section: What Kind Of Induction Therapy Should We Choose For Such An ...mentioning
confidence: 99%
“…Savolitinib is an oral, potent and highly selective type Ib MET inhibitor that has yielded promising activity and acceptable safety profile in patients with pulmonary sarcomatoid carcinoma and other NSCLCs harboring METex14m (2). Recently, a growing body of research has shown the feasibility of the neoadjuvant targeted therapy for early-stage resectable NSCLC patients with anaplastic lymphoma kinase (ALK) fusion gene, epidermal growth factor receptor (EGFR) mutations, RET rearrangements and ROS proto-oncogene 1 (ROS1) rearrangements (3)(4)(5)(6). The fact suggests that the untargeted patients with METex14m had a shorter disease-free survival (DFS) (7).…”
Section: Introductionmentioning
confidence: 99%